(untitled) (Research, Society and Development, 2020)
The textbook is an important tool in school learning, serving as a bridge to approach complex content and make academic-scientific language accessible to the student age group. Taking into account its relevance, the objective of this work was to characterize the specialized knowledge on the theme of Climate Crisis present in Biology textbooks, indicated by the National Textbook Program (2018-2020), using the Specialized Knowledge Model of Teachers of Biology as a methodological tool. The theme was analyzed in the first or third year books of six didactic collections, where we highlight excerpts from the books that were configured as teaching episodes containing specialized knowledge. In the six analyzed works, we identified a total of 148 specialized knowledge according to the Specialized Knowledge model of Biology Teachers. We realize that the thematic climate crisis is worked on in a critical and reflective way in textbooks, but some excerpts analyzed may develop in students the feeling that nothing is done to solve this problem, mischaracterizing the effort of national and international research institutions to produce studies on the impacts arising from the climate crisis and its mitigation measures. In the current political panorama of our country, it is of great importance to talk about the climate crisis, since the negationism grows as the government takes advantage of the social incredulity about the environmental catastrophes, commonly experienced in Brazil and in the world, intensified by the development in the various economic sectors, which make their long-term impacts invisible to the environment and society.